Replicative capacity of β-cells and type 1 diabetes. (July 2016) - Saunders, Diane; Powers, Alvin C.
Abstract: Efforts to restore β-cell number or mass in type 1 diabetes (T1D) must combine an intervention to stimulate proliferation of remaining β-cells and an intervention to mitigate or control the β-cell-directed autoimmunity. This review highlights features of the β-cell, including it being part of a pancreatic islet, a mini-organ that is highly vascularized and highly innervated, and efforts to promote β-cell proliferation. In addition, the β-cell in T1D exists in a microenvironment with interactions and input from other islet cell types, extracellular matrix, vascular endothelial cells, neuronal projections, and immune cells, all of which likely influence the β-cell's capacity for replication. Physiologic β-cell proliferation occurs in human and rodents in the neonatal period and early in life, after which there is an age-dependent decline in β-cell proliferation, and also as part of the β-cell's compensatory response to the metabolic challenges of pregnancy and insulin resistance. This review reviews the molecular pathways involved in this β-cell proliferation and highlights recent work in two areas: 1) Investigators, using high-throughput screening to discover small molecules that promote human β-cell proliferation, are now focusing on the dual-specificity tyrosine-regulated kinase-1a and cell cycle-dependent kinase inhibitors CDKN2C/p18 or CDKN1A/p21as targets of compounds to stimulate adult human β-cell proliferation. 2) Local inflammation, macrophages, and the local β-cell microenvironment promote β-cell proliferation. Future efforts to harness the responsible mechanisms may lead to new approaches to promote β-cell proliferation in T1D. Highlights: New approaches needed to overcome β islet cell's low proliferative capacity. Physiologic/pharmacologic approaches to stimulate β-cell proliferation discussed. Small molecules promote β-cell proliferation in vitro . Macrophage and islet microenvironment promote β-cell proliferation in vivo.